Hepatocellular carcinoma recurrence in the extrahepatic bile duct wall: A case report. Issue 3 (26th January 2021) - Matsumoto, Taku; Yoshida, Toshihiko; Yamagishi, Takashi; Goto, Hironobu; Otsubo, Dai; Furutani, Akinobu; Yamane, Hisoka; Fujino, Yasuhiro; Tominaga, Masahiro
Abstract: We should know that hepatocellular carcinoma can progress as if it replaces the bile duct wall itself. Abstract : We should know that hepatocellular carcinoma can progress as if it replaces the bile duct wall itself.